2018
DOI: 10.24042/tadris.v3i2.3114
|View full text |Cite
|
Sign up to set email alerts
|

Development of Interactive E-book on Energy Resources to Enhance Student’s Critical Thinking Ability

Abstract: This research aimed to develop a valid interactive e-book using Learning Content Development System (LCDS) with scientific approach on energy resources to enhance student’s critical thinking ability, to know readability and the ease of operating the developed e-book. The method used is research and development. The implementation of procedures adopted from Sugiyono’s design which consisted of 7 adjusted steps that were potency and problem assessment, data collecting, developing preliminary form of product, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 1 publication
(2 reference statements)
0
2
0
2
Order By: Relevance
“…Hasil perhitungan effect size pada tabel 5 menunjukkan bahwa secara keseluruhan pembelajaran mandiri dengan e-book interaktif yang dikembangkan berdampak positif dengan kekuatan ukuran 0,72 yang diinterpretasikan pada kategori cukup berdampak dibandingkan dengan pembelajaran menggunakan buku cetak. Analisis efektivitas ini juga sejalan dengan hasil-hasil penilitian terdahulu yang menunjukkan penggunaan ebook interaktif berdampak untuk melatihkan keterampilan berpikir kritis dibandingkan dengan modul cetak (Hasan et al, 2018) (Pradina & Suyatna, 2018) (Suyatna et al, 2018).…”
Section: Efektivitas E-book Interaktifunclassified
“…Hasil perhitungan effect size pada tabel 5 menunjukkan bahwa secara keseluruhan pembelajaran mandiri dengan e-book interaktif yang dikembangkan berdampak positif dengan kekuatan ukuran 0,72 yang diinterpretasikan pada kategori cukup berdampak dibandingkan dengan pembelajaran menggunakan buku cetak. Analisis efektivitas ini juga sejalan dengan hasil-hasil penilitian terdahulu yang menunjukkan penggunaan ebook interaktif berdampak untuk melatihkan keterampilan berpikir kritis dibandingkan dengan modul cetak (Hasan et al, 2018) (Pradina & Suyatna, 2018) (Suyatna et al, 2018).…”
Section: Efektivitas E-book Interaktifunclassified
“…Penelitian yang dilakukan Suprapto, Apriandi, & Pamungkas (2019) menghasilkan produk yang dikembangkan sangat layak digunakan untuk membantu guru dalam menunjang proses belajar di kelas. Hasan, Suyatna, & Suana (2018) dalam penelitiannya mengungkapkan the products developed are of very good quality and fit for use. Harjono, etal (2020) dalam hasil penelitiannya juga mengemukakan bahwa product development that is carried out is effective in increasing the mastery of concepts in students.…”
Section: Pendahuluanunclassified
“…Sehingga dengan adanya pengembangan e-book interakif mampu mempermudah siswa pada saat memahami materi dengan memberikan kemudahan adanya kelengkapan gambar dan kesesuiannya isi dalam e-book dengan yang ada di lingkungan. Hasan, Suyatna, & Suana (2018) dalam penelitiannya memperoleh hasil e-book interaktif yang berhasil dikembangkan menunjukkan layak untuk dipergunakan. Penelitian oleh Wardani, Degeng, & Cholid (2019) juga menyatakan bahwa "interactive multimedia developed to get good qualifications to be used in helping the learning process".…”
Section: Kelayakan Pengembangan Bahan Ajar Interaktif Berbasis Case (...unclassified
“…This study covered the development process of an interactive e-book based on the POE method by choosing "heat and temperature" from among physics topics. In the literature, a limited number of interactive e-books have been developed on physics, and they are related to energy sources (Hasan et al, 2018), static liquids (Adam & Suprapto, 2019), rotational dynamics (Adawiyah et al, 2019;Harjono et al, 2020), momentum (Septikasari et al, 2021), and earthquakes (Perwita & Fauzi, 2021). However, the literature review found no interactive e-books developed for the "heat and temperature" topic.…”
Section: The Processes Experienced During the Analysis Phasementioning
confidence: 99%
“…As research sample, previous studies in the interactive e-books field covered university students (Almekhlafi, 2021;Kao et al, 2019), preschool students (Li et al, 2020;Mouri et al, 2018;Sung & Wu, 2017), or primary school students (Huang & Liang, 2015;Hwang & Lai, 2017;Sung et al, 2019a, b;Umarji et al, 2020). There were a limited number of studies on physics subjects with high school students (Adam & Suprapto, 2019;Adawiyah et al, 2019;Harjono et al, 2020;Hasan et al, 2018;Perwita & Fauzi, 2021;Septikasari et al, 2021). In this sense, the interactive e-book developed in the study contributed to the literature on physics education at the high school level.…”
Section: The Processes Experienced During the Analysis Phasementioning
confidence: 99%